Chronic institutional failure and enhanced vulnerability to flash‐floods in the Cuenca Altadel Río Lerma, Mexico. Issue 1 (13th August 2015) - Güiza, Frida; Simmons, Peter; Burgess, Jacquie; McCall, Michael K.
Abstract : The dominant paradigm in disaster risk reduction (DRR) policies has been seriously contested because of its reliance on interventions based on technocratic expertise. In the Mexican context, the influence of informal practices such as clientelism and cartelisation of the political system produces environmental degradation and vulnerability to disasters within the communities in the study site. This paper contributes to understanding of failed institutional processes and parallel practices that intensify vulnerability to disasters by contrasting the discourses of agents within a peri‐urban community in central Mexico. Employing the Situational Analysis Approach as a methodological framework, the study identifies divergent views and practices within the community, leading to different responses to disasters and to different perceptions regarding institutional performance. In addition, it finds that institutional decision‐making, based only on scientific and technical expertise, has resulted in unintended consequences that influence ongoing vulnerability to floods in the site under review.